MANAJEMEN SUMBER DAYA PENDIDIK DALAM PENINGKATAN KINERJA GURU PADA MADRASAH IBTIDAIYAH NEGERI DI KOTA BANDAR LAMPUNG - Santika, Desi; Hadiati, Eti; Septuri , Septuri (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Educator resource management has a direct impact on teacher performance, which in turn affects the quality of education in the madrasah environment. The purpose of this study is to analyze how human resource management, especially through the stages of recruitment and selection, training and development, performance assessment, and awarding, contributes to improving teacher performance at Madrasah Ibtidaiyah Negeri (MIN) in Bandar Lampung City. This study uses a qualitative descriptive type of research. Data from primary and secondary data. The data collection technique was through in-depth interviews with the head of the madrasah, Administrative Staff, Teachers, as well as observation and documentation. Data analysis techniques use data reduction, data presentation, and data verification. As well as in checking the validity of the data using source triangulation.  Based on the results of the study, it is shown that: (1) The recruitment and selection process of educators is carried out by optimizing bezetting data, relational approaches, and strict administrative filing, demonstrating the effective implementation of recruitment principles; (2) Teacher development and training involves various programs, including the PINTAR program from the Ministry of Religious Affairs, with a sustainable approach and strategic partnerships; (3) Teacher assessment and appreciation emphasizes on achieving performance targets and contributing to improving student achievement. ABSTRAKManajemen sumber daya pendidik (SDM) memiliki dampak langsung pada kinerja guru, yang pada gilirannya memengaruhi kualitas pendidikan di lingkungan madrasah. Tujuan penelitian ini adalah untuk menganalisis bagaimana manajemen SDM, khususnya melalui tahapan rekrutmen dan seleksi, pelatihan dan pengembangan, penilaian kinerja, serta pemberian penghargaan, berkontribusi pada peningkatan kinerja guru di Madrasah Ibtidaiyah Negeri (MIN) di Kota Bandar Lampung.Penelitian ini menggunakan jenis penelitian  deskriptif kualitatif. Sember data dari data primer dan sekunder. Teknik pengumpulan data melalui wawancara mendalam kepada kepala madrasah, Staff Administrasi, Guru, juga observasi serta dokumentasi. Teknik analisis data menggunakan reduksi data, penyajian data,  dan verifikasi data. Serta dalam memeriksa keabsahan data menggunakan triangulasi sumber.  Berdasarkan hasil penelitian menunjukkan bahwa: (1) Proses rekrutmen dan seleksi tenaga pendidik dilakukan dengan optimalisasi data bezetting, pendekatan relasional, dan pemberkasan administrasi yang ketat, menunjukkan implementasi prinsip-prinsip rekrutmen yang efektif; (2) Pengembangan dan pelatihan guru melibatkan berbagai program, termasuk program PINTAR dari Kementerian Agama, dengan pendekatan berkelanjutan dan kemitraan strategis; (3) Penilaian dan penghargaan guru menekankan pada pencapaian target kinerja dan kontribusi terhadap peningkatan prestasi siswa.